1989
DOI: 10.1038/bjc.1989.10
|View full text |Cite
|
Sign up to set email alerts
|

In vitro photosensitization of tumour cell enzymes by Photofrin II administered in vivo

Abstract: Dougherty, 1979). After 24-72h, to allow clearance of the photosensitiser from normal tissues, the malignant lesions are exposed to visible light, usually by laser irradiation. Tumour necrosis and regression ensue from photoradiation. It is generally agreed that cytotoxicity is mediated via formation of the highly reactive oxygen species, singlet oxygen, 102, (Weishaupt et al., 1976;Gibson et al., 1984;Parker, 1987). Since the original promising clinical results utilised HpD, a crude preparation composed of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Previously, after i.p. administration of either HpD or Photofrin II, a time course of photosensitivity of these organelles in vitro indicated that inhibition of mitochondrial function would be greatest when tumours were exposed to light 24-72 h after drug administration (Gibson et al, 1989). Intratumoral administration of Photofrin II, however, showed a different time-course.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previously, after i.p. administration of either HpD or Photofrin II, a time course of photosensitivity of these organelles in vitro indicated that inhibition of mitochondrial function would be greatest when tumours were exposed to light 24-72 h after drug administration (Gibson et al, 1989). Intratumoral administration of Photofrin II, however, showed a different time-course.…”
Section: Discussionmentioning
confidence: 97%
“…For study of mitochondrial effects, the in vivo-in vitro protocol was employed, an approach that takes into account any host metabolism and intracellular localisation of the photosensitiser occurring in vivo (Gibson & Hilf, 1983;Gibson et al, 1984bGibson et al, , 1989. From such data, we can derive an estimate of the pharmacokinetics of the administered photosensitiser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoperoxidation of membrane cholesterol and other unsaturated phospholipids leads to changes in membrane permeability, loss of fluidity, cross-linking of aminolipids and polypeptides, and inactivation of membrane associated enzyme systems and receptors (Girotti, 1990). While the inhibition of mitochondrial enzymes has frequently been considered a key event in PDT cell lethality (Gibson et al, 1989;Salet and Moreno, 1990), there is evidence that the inactivation of membrane transport systems, depolarization of the plasma membrane and inhibition of DNA repair enzymes may precede inactivation of mitochondrial, cytosolic and lysosoma1 enzymes ; Boegheim et a f . , Specht and Rodgers, 1990).…”
Section: Cellular Effectsmentioning
confidence: 99%
“…Damage to mitochondrial functions leads to irreversible cell inactivation. The photosensitization may inhibit a number of mitochondrial enzymes: cytochrome C oxidase, FoFl ATPase, succinate dehydrogenase, NADH dehydrogenase (Gibson et a/., 1989;Hilf et al, 1984), adenylate kinase and monoamine oxidase (Murant et a/., 1987). Suppression of mitochondrial activity after PCT leads to a significant reduction in the cellular ATP level and, consequently, to a loss of viability (Hilf et al, 1986).…”
mentioning
confidence: 99%